Changes in prescription patterns in older hospitalized patients: the impact of FORTA on disease-related over- and under-treatments - Pazan, Farhad; Burkhardt, Heinrich; Weiß, Christel; Wehling, Martin (European journal of clinical pharmacology, 2018)
PurposePhysicians often face difficulties in choosing appropriate medications for multimorbid older people. The FORTA (Fit for the Aged) classification (A: absolutely, B: beneficial, C: careful, D: don’t) was proposed as a clinical tool for improving the quality of drug treatment in the aged. As an implicit tool, FORTA has been shown to aid medication optimization and improve clinical end points in the VALFORTA trial. In this prospective randomized controlled study, 207 older hospitalized patients received standard geriatric treatment and 202 patients received FORTA-guided treatment.MethodsHere, changes of drug prescriptions at the anatomical-therapeutic-chemical system (ATC) level were evaluated separately for important diagnoses in descriptive analyses; over- and under-treatment rates were compared between groups.ResultsAt the individual drug/drug class level related to all important diagnoses, the application of FORTA significantly improved under-treatments for 12 drugs/drug classes (e.g., ACE inhibitors to treat arterial hypertension) and over-treatments for 7 drugs/drug classes (e.g., proton pump inhibitors to treat gastroesophageal reflux disease).ConclusionsFORTA representing the first combined positive/negative labeling approach at the individual drug level aids the optimization of drug treatment in older people as detected for drugs/drug classes at the ATC level in important indications. FORTA is effective in addressing over- and under-treatments even if analyzed for smaller subgroups of VALFORTA.
Published online: 02 December 2017
Gesehen am 03.07.2018